2020
DOI: 10.29333/ejmste/7893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on the Performance of Grade 12 Students: Implications for STEM Education

Abstract: With all learning institutions prematurely closed on 20 March 2020 and all citizens advised to self-isolate in a bid to control the spread of COVID-19, it was hypothesized that COVID-19 would negatively impact on the performance of students in the 2020 Grade 12 national examinations vis-à-vis mathematics, science and design and technology subjects. An observed steady increase in the number of COVID-19 confirmed cases and the low levels of technology use in secondary schools in Zambia due to limited technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
491
2
88

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 611 publications
(597 citation statements)
references
References 6 publications
16
491
2
88
Order By: Relevance
“…This pauses a great danger and an outbreak like COVID-19 can rapidly spread. This is consistent with (Sintema, 2020) who also posited that schools are the breeding grounds and dangerous places for the spread of the virus. Because of this most students or learners are forced to be in their homes.…”
Section: Covid-19 and Digital-learning Platforms In Zambiasupporting
confidence: 88%
“…This pauses a great danger and an outbreak like COVID-19 can rapidly spread. This is consistent with (Sintema, 2020) who also posited that schools are the breeding grounds and dangerous places for the spread of the virus. Because of this most students or learners are forced to be in their homes.…”
Section: Covid-19 and Digital-learning Platforms In Zambiasupporting
confidence: 88%
“…A recent study of high school students suggested that school closures and concerns over COVID-19 are significantly impacting performance of students in their subject areas ( Viner et al, 2020 ) and will continue to have a lasting impact on our education system. While limited data is available, similar educational and economic impacts are also being found outside of the United States ( Sintema, 2020 ).…”
Section: Related Workmentioning
confidence: 85%
“…Different studies have shown that although there are some examples of having a plan of using the distance/online learning during the pandemic, they are mostly concentrated on small cases and not a global crisis as it is happening in COVID-19 pandemic of 2020. Especially the countries that are having the limited technologies have problems in schools are not ready for the complete implementation of the countrywide online education (Sintema J, 2020). Results of different studies shows that the virtual teaching environments can be successfully used in school or higher education in case of having appropriate technical environment and support.…”
Section: Related Literaturementioning
confidence: 99%